Guide of care: caring and daily care of clients with mitral valve implant - Dutra, Cristina Maria Pereira (2009)
Exploratory descriptive research, quantitative and thematic analysis. Object of study the elaboration of a Guide of Care for the clients submitted to mechanical mitral valve implant. Objectives: trace clients’ profile with mechanical mitral valve; identify challenges and needs of these clients; evaluate the possibilities of self caring by these clients, analyze themes and components that should be shared to these clients through the guide of care, elaborate a mitral valve user’s guide with care for post-discharge. Theoretical foundation observed the concepts of caring/care, elaborated by researchers on the nursing care area: Waldow (1992, 1994, 1995, 1998); Neves Arruda (1993), Silva (1993, 1995, 1997a, 1997b), Coelho (1999), Figueiredo y Carvalho (1999), Santoro (2002) and on education: Freire (2003). Scenery was the out patients’ unit of cardiology in a public hospital in Rio de Janeiro. To obtain data, it was utilized a semi-structured interview, with forty-eight clients of both sexes, ranging from 20 to 59 years old.  It was concluded that after hospital discharge, everyone manifest physical and temporal impediments alike, owing to the surgery to which they were submitted; social-economical questions contributed to aggravate physical and emotional conditions; family support is of fundamental importance to client recovery, as well as regular ambulatory revisions. Through these results, it was elaborated an Guide of Care prototype, validated by clients and further graphically improved, contained information / explanation scientifically elaborated on the main problems related to subject of the study, and how to carry out care properly, aiming to momentary recovery which present it. The presentation form is simple and, undoubtedly, the compound is significantly important for client in post-hospital discharge period, allowing them not only solving doubts, but also making relevant notes Therefore, as a final expression of research, it is a document in which systematized nursing care has the objective of the best client recovery and warrant of life quality.Key words: Nursing; Care; Cardiac Surgery; Mitral valve.